THE ROLE OF PRAGMATICS IN SPOKEN COMMUNICATION - Teshaboyeva Nafisa Zubaydulla qizi,; Xamidova Mashxura Abror qizi, (Ustozlar uchun, 2025)
Effective spoken communication is more than just using correct grammar or vocabulary; it is the ability to convey and interpret meaning appropriately depending on the context. This deeper layer of communication is governed by pragmatics.